2009
DOI: 10.1007/s00415-009-5074-x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of l-amphetamine sulfate on cognition in MS patients: results of a randomized controlled trial

Abstract: Defects in processing speed and memory are common in multiple sclerosis (MS) patients. In other populations, amphetamines have been shown to enhance cognition, but their use is limited by adverse behavioral effects. The L-isomer may have equivalent cognition enhancement with less adverse effects due to decreased potency in subcortical areas. The aim of this study was to assess the safety and efficacy of L-amphetamine sulfate in the treatment of cognitive dysfunction in MS. This was a 2:1 randomized, placebo-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(25 citation statements)
references
References 41 publications
1
22
0
2
Order By: Relevance
“…Initially there were encouraging data showing that l-amphetamine 13 and donepezil 14 can be effective for improving processing speed and memory defects, respectively. 15,16 Unfortunately, these studies were not replicated in subsequent research. Despite the lack of evidence, 58% of MS health-care providers in the survey indicated that they prescribe a variety of medications to improve cognitive symptoms in MS.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Initially there were encouraging data showing that l-amphetamine 13 and donepezil 14 can be effective for improving processing speed and memory defects, respectively. 15,16 Unfortunately, these studies were not replicated in subsequent research. Despite the lack of evidence, 58% of MS health-care providers in the survey indicated that they prescribe a variety of medications to improve cognitive symptoms in MS.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…By contrast, an earlier study found either no difference or minor impairments on a range of 202 cognitive tasks (e.g., symbol copy, digit symbol) when those with schizophrenia were administered D-amphetamine (10 or 20 mg; Kornetsky, 1976). L-Amphetamine, administered orally in increasing doses throughout a 29-day period (5 mg for days 1-7, 15 mg for days 8-14, and 30 mg for days 15-29), enhanced verbal and spatial memory in cognitively impaired multiple sclerosis patients (Morrow et al, 2009). D-Amphetamine, compared with placebo in a double-blind study, enhanced recovery from aphasia in stroke patients who were administered 10 mg of drug 30 minutes before speech therapy for 1 week (Walker-Batson et al, 2001).…”
Section: Amphetaminementioning
confidence: 99%
“…In a pilot double-blind, placebo-controlled study involving 19 MS patients [43], single 45 mg doses of L-amphetamine sulfate in MS were associated with improved performance on information processing speed. Morrow et al [44] tested 151 clinically definite MS patients randomized to L-amphetamine or to placebo in a 6-week. The trial results did not confirm any significant improvement on Symbol Digit Modalities Test (SDMT) or on the subjective ratings of cognition.…”
Section: Symptomatic Drugsmentioning
confidence: 99%